Sleep Restriction and Time-of-Day Impacts on Simple Social Interaction - David L. Dickinson; Todd McElroy (Institute for the Study of Labor (IZA), 2016)
Simple bargaining games are the foundation of more complex social interactions necessary for healthy relationships and well-functioning societies. Neuroscience research has shown that high-level deliberative thinking processes are necessary for social-decision making - it seems cognitively less demanding to be greedy or to mistrust. In this paper, our focus is on how commonly-experienced adverse sleep states, which are known to harm deliberative thinking, impact outcomes in the classic simple bargaining games (ultimatum, dictator, and trust games). Specifically, we experimentally manipulate sleep states of 184 young-adult subjects who took part in a 3 week experimental protocol. Subjects were administered each game twice: once after a full week of sleep restriction and once after a full week of well-rested sleep levels. Subjects were also randomly assigned to early morning (7:30 am) or later evening (10:00 pm) sessions to manipulate the optimality of the time-of-day of the decisions. We find a robust result of increased greed, reduced trust, and reduced trustworthiness following sleep restriction, after controlling for demographics and session indicators. We find no significant direct impact of circadian timing on decisions for these tasks. However, the mediating variable for these sleep manipulation effects is subjective sleepiness, and both sleep restriction and suboptimal circadian timing significantly increase self-reported sleepiness. These results are consistent with the hypothesis that increased sleepiness reduces the relative input of deliberate thinking in social interactions.
Keywords: C7; C9; 330; sleep; time-of-day; ultimatum; dictator; trust; bargaining